Evaluation of Conservation Education Implementation in Elementary Schools Located Near Conservation Areas in Wirajaya Bogor - Selanova Nurdina; Endang Koestati Sri Harini Muntasib; Resti Meilani; Burhanuddin Masyud (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Conservation education is essential for communities living near conservation areas to support environmental sustainability and ecosystem preservation. Wirajaya, Jasinga, Bogor, is located near Gunung Halimun Salak National Park and Dungus Iwul Nature Reserve. However, this geographical proximity has not been accompanied by adequate conservation understanding, particularly in elementary school settings. This study aims to evaluate the implementation of conservation education in elementary schools in Wirajaya by analyzing the curriculum and students’ and teachers’ conservation-related knowledge, attitudes, and behaviors. The study was conducted in three elementary schools, namely SDN Curug 03, SDN Curug 05, and SDN Cigelung, involving 86 fifth-grade students and 9 teachers as research participants. Data were collected through curriculum document analysis, interviews, and field observations. The results reveal that conservation content has not been systematically integrated into the school curriculum. The topics taught were still limited to environmental cleanliness, greening activities, waste management, and an introduction to biodiversity. Students’ knowledge and teachers’ understanding of conservation remained limited. This study provides an initial overview of conservation education implementation in elementary schools near conservation areas, highlighting curriculum, teacher and student understanding, and local conservation areas as learning resources.